Ancient Schawanoma of radial nerve: a rare case report - Mujahid, Abdul Malik; Saad, Asma Binte; Alam, Iftikhar; Khan, Husnain (Journal of the Pakistan Medical Association, 2024)
Soft tissue swellings on the forearm can present with a range of clinical and histopathological diagnosis. Ancient Schawanoma is a rare benign condition that can develop over the flexor surface of the forearm as a cystic swelling and can involve the median or the ulnar nerve. However, the presentation of this condition on the extensor surface with involvement of the radial nerve is an extremely uncommon diagnosis. A 69 year old female presented at the outpatient department with a swelling on the extensor aspect of her right forearm for the past 2 years. Ultrasound examination showed a mixed cystic solid mass and MRI report revealed a complex predominantly cystic mass in the extensor compartment of the forearm, measuring 4.3 x 5.3 x 7.2 cm size. ---Continue